Homologous recombination can restore normal immunoglobulin production in a mutant hybridoma cell line. - Baker, M D (1988)
We report here the occurrence of homologous recombination between transferred and chromosomal immunoglobulin genes. Specifically, we have corrected a chromosomal immunoglobulin gene mutation by transferring pSV2neo vectors encoding the constant region of the immunoglobulin mu heavy chain to mutant hybridoma cells that bear a 2-base-pair deletion in the third constant region exon of their chromosomal mu gene. After DNA transfer, we detected G418-resistant transformants that produce normal IgM. Analysis of the DNA structure of the mu gene in these transformants indicates that in four of five cases the mu gene has been restored as a result of the integration of a single copy of the transfer vector by a reciprocal homologous recombination event; the fifth case seems to have resulted from gene conversion or double crossover. These results suggest that this technology might be adapted for mapping immunoglobulin gene mutations by marker rescue and for more convenient engineering of specifically altered immunoglobulin.